Retrospective analysis of management of patients presenting with acute urinary retention due to benign prostatic hyperplasia: A hospital based study - Pandit, RK; Agrawal, CS; Chalise, PR; Sapkota, G (Kathmandu University Medical Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Objectives: To analyze current practice of management of acute urinary retention (AUR) in men above 40 years of age at B.P.Koirala Institute of Health Sciences, Nepal. Materials and methods: A total of 68 patients (aged 50-91 years) presenting with indwelling catheter for AUR were included in the study. Because of lack of clear guideline and limited health care facility in our setup trial without catheter (TWOC) was given selectively depending mainly on preexisting symptoms. AUR presumed to be due to urinary tract infection received only antibiotic and others diagnosed of benign prostatic hyperplasia (BPH) received alfa1 blocker prior to TWOC. TWOC was given 3-15 days after such treatment. Those satisfied without catheter for at least a week were considered successful TWOC. Results: The data was available for 68 patients (mean age 66.1 years). Of 15 patients treated with antibiotic alone, 11 (73.3 %) had successful TWOC. Of 57 with presumptive diagnosis of BPH, 68.9% (31 of 45) had successful TWOC. Mean age, symptom score and prostate volume were higher for patients with unsuccessful TWOC. Conclusion: Selective TWOC may be imperative to minimize unnecessary suffering from AUR in less easily accessible health care facilities like ours. It may also reduce total cost of treatment. Key words: Acute urinary retention, benign prostatic hyperplasia, trial without catheter doi: 10.3126/kumj.v6i4.1733 Kathmandu University Medical Journal (2008), Vol. 6, No. 4, Issue 24, 448-452